96: POSITION RESEARCH AND CRITICAL THINKING IN CLINICAL NURSES' PROFESSIONAL COMPETENCIES. (8th February 2017) - Farokhzadian, Jamileh; Forughameri, Golnaz; Karami, Abbas
Abstract : Background and aims: Nurses are one of the main components of health care system and due to clinical tasks they must have the technical, research and critical thinking skills. Professional competencies are a fundamental and basic concept in nursing, which has a direct relationship with public health and it is an important factor in providing the high-quality care and can guarantee the quality of care. With regard to the importance of this category in healthcare organizations and finally the health of society, this study was conducted to investigate the professional competencies of nurses. Methods: The statistical population of this descriptive-sectional study included all nurses working in hospitals affiliated to Rafsanjan University of Medical Sciences in 2016. A total number of 230 nurses were selected using stratified random sampling and sample size formula. Data were gathered by two questionnaires include socio-demographic information and Competency Inventory for Registered Nurse (CIRN). Statistical analysis was performed using descriptive statistics (mean and standard deviation) and statistics analysis (Mann-Whitney, Kruskal-Wallis) and SPSS version 18. Results: The meanest score of professional competencie according to the Likert scale related to Legal/ethical practice dimension (3.13±0.6) and the least mean score related Research aptitude and Critical thinking dimension (2.7±0.67). The statistical analysis showed that the mean score of professional competence was significantly higher among married nurses than single nurses (p=0.031). In addition, the highest mean score of professional competences belonged to the nurses with at least 15-year work experience (p=0.001). Conclusion: Due to the low position of research and critical thinking in clinical nurses' professional competencies, It is essential for nursing managers to increase in level of nurses' professionalism and promote the quality of research-based care through take appropriate measures such as identify interpersonal and intrapersonal factors influencing the professional competence and design and implementation of training and management programs covering all dimensions of professional competence.